Research on 3D Visualization Simulation System of Deck Crew Based on OpenGL Technology. (May 2020) - Yan, Shiwei; Wang, Wei; Geng, Jianming; Wang, Nengjian; Liu, Qinhui
Abstract: Based on OpenGL technology, a SGR simulation system which including virtual human operation was designed. The motion control of the virtual human was realized by using local finite state machine under the action of the control, and obstacle avoidance method for the virtual human was realized. Compared with the simulation programs developed with Vega Prime, this simulation speed obviously has advantages and the requirements on the computer are also lower.